Managing emotions - Palanca, Peter (Boston, MA : Allyn & Bacon Professional, 2002)
In this tape, Peter Palanca takes a group of participants through the steps of recognizing emotions, accepting them, and deciding on approriate responses. The group members discuss anger, grandiosity, shame, and guilt
Editor, Virginia Lanigan
Moderator: Jon Carlson, Judy Lewis
Keywords: Emotions; Conduct of life; Behavior modification